PERSEPSI PENGUNJUNG TERHADAP MUSEUM SANG NILA UTAMA PEKANBARU - Fareira T, Anton; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the Museum Sang Nila Utama on the road Jendral Sudirman No.194 Tangkerang Tengah Marpoyan Damai Pekanbaru city. With the formulation of the problem (1) how the characteristics of visitor’s to the museum Sang Nila Utama Pekanbaru (2) how the visitor’s perception of the physical condition of the Museum Sang Nila Utama Pekanbaru (3) how the relationship between museum visitor’s perception of the physical condition of the museum with the level of visitor’s understanding of the historical value of the collection museum Sang Nila Utama Pekanbaru. The purpose of this study is to analyze the Characteristics of visitors Museum Sang Nila Utama Pekanbaru, to analyze visitor perceptions of the physical condition of the Museum Sang Nila Utama Pekanbaru, and to determine the relationship between visitor perceptions of the physical condition of the museum with the level of understanding of visitors to the historical value of collections Museum Sang Nila Utama Pekanbaru. This research is descriptive research with quanttitative approach. The population in this study as many as 100.017 people, then in use one of the sampling technique that is by using slovin method then the sample can be as much as 99 people. The collect this research data in quetionnaire and documentation. Based on the result of the study can be concluded that (1) in general visitors Museum Sang Nila Utama have used the museum function well, from 99 respondents there are 50 respondents with a percentage of 58.6 % with high category in formal activities, and from 99 respondents there are 42 respondents 71.2 % on non formal activities (2) there are 25 respondents 25.3 % who have a negative perception, and 74 respondents 74.7 % who have positive perception on the physical condition of the Museum Sang Nila Utama Pekanbaru. (3) The correlation between visitor’s perception toward physical condition of the museum with the level of visitor’s understanding on the historical value is 0.755 (75.5 %) and the relation is strong and can be stated that Ha is accepted which means that there is correlation between visitor perception to physical condition of the Museum with the level of visitor understanding history of collections Museum Sang Nila Utama Pekanbaru.Keywords : Perception, Historical Value, Museum